PENGEMBANGAN DESAIN KEMASAN KERIPIK MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) (STUDI KASUS PADA UKM MPOK IMEH) - Yuyun Yuniar Rohmatin; Rossi S. Wahyuni; Mei Raharja (Jurnal Konversi Energi dan Manufaktur, 2023)
Mpok Imeh Chips is an Independent small business that produces Balado cassava chips in Jakarta, where cassava chips are packaged using plain plastic so that it has an unattractive impression. This research focuses on developing packaging designs that are following customer desires using the quality function deployment (QFD) method. Based on the results of the study, it is known that the customer's requirement for cassava chip packaging produced by UKM Mpok Imah includes cassava chip packaging that functions to protect the product, a medium packaging size. The form packaging is a standing pouch. Cassava chips packaging is made of polypropylene plastic transparent packaging. There is product information on the packaging. The packaging design is based on the house of quality (HOQ) in QFD and uses polypropylene plastic materials, size (14 x 22) cm, a weight of 250 grams, cassava chips illustration, transparent and a standing pouch packing, description on the label shown on the front view design shows a visualization of the chip's packaging, there is some information about the product including the product name, net weight, address of the producing party and the halal logo. On the back packaging shown, there is information about the composition, storage rules and how used the packaging information expiration date of the packaged product.